Seymour Menton, Latin America's New Historical Novel - Hampe Martínez, Teodoro (1994)
SEYMOUR, MENTON. Latin America's New Historical Novel. Austin: University of Texas Press, 1993. x, 228 p. (Texas Pan American Series). ISBN 0-292-75157-5.